Bio-Stimulants Extend Shelf Life and Maintain Quality of Okra Pods - Abdel-Haleem A. H. El-Shaieny; Naglaa A. A. Abd-Elkarim; Eman M. Taha; Sayed Gebril (Agriculture, 2022)
Okra (Abelmoschus esculentus L.), a tropical annual crop, is a highly perishable vegetable. Okra pods deteriorate rapidly after harvesting. The pods undergo physical and physiological changes that diminish storability and quality. The purpose of this study was to investigate the effect of bio-stimulants on the storability and quality of okra pods stored at 4 °C and 25 °C for 12 days. Dipping okra pods for 5 min in a solution of 0.5% ascorbic acid, citric acid, or salicylic acid pre-storage significantly extended the shelf life and preserved the quality of the pods compared to the control condition at 4 °C and 25 °C. Citric acid and ascorbic acid were the most effective in preserving most traits. Citric acid reduced the loss in weight, firmness, appearance, and prevented decay at 4 °C and 25 °C. Ascorbic acid decreased the loss of moisture and the degradation of carbohydrates, vitamin C and lycopene at 4 °C and 25 °C. Salicylic acid decreased the degradation of protein at 25 °C. The low temperature was highly effective in decreasing the loss or degradation of most of the studied traits. Taken together, bio-stimulants and storing at 4 °C played a prominent role in extending the shelf life and preserving the quality of okra pods.